Impact of trust on online relationship banking: empirical evidence from Colombo district, Sri Lanka - Muthusamy, V.; Vithanawasam, D.V.T. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
Managing consumers’ trust is a critical issue for most of the banks in Sri Lanka. Especially consumers’ trust is very important determinant to enhance online banking relationship commitment. This research was focused on to explore the relationship between the key antecedents of (Communication, Opportunistic Behaviour, Security and Privacy) online customer trust in Sri Lankan context. Flowingly, the researcher focused to investigate how the trust impact on the online relationship commitment in Colombo District. The population was unknown the researcher was selected 384 respondents based on non-probability sampling method and under the convenience sampling the self-administered standard structured questionnaire was distributed through online to collect data for the study. The multiple and simple linear regression model results indicated the emails and other social media websites. The results of the study indicated that the communication, security and privacy have a positive and significant impact on consumers’ trust in online banking transaction and Opportunistic behaviour has significant negative impact on consumer’s trust and also finds higher perceived trust to enhance significantly customers’ commitment in the online banking transaction. Findings of this study provide an implication for the Board of Directors should focus on the privacy of the online customers and also the security enhancement. Most importantly the bankers have to continuously expose the good side of the online services to the offline clients. In future researchers have to identify how trust is developed and sustained over different levels of customer relationships in online banking.
Keywords: online banking; relationship commitment; Sri Lanka; trust